Description of a new genus and species of Eucoilinae (Hymenoptera: Cynipoidea: Figitidae) parasitoid of Ephydridae (Diptera) - Díaz, Norma Beatriz (2009)
Hydrelliaeucoila egeria (Hymenoptera: Cynipoidea: Figitidae), a new genus and species obtained from pupae of Hydrellia sp. (Diptera: Ephydridae) mining in Egeria densa Planchon (Hydrocharitaceae), is described. Diagnostic photographs and data about the biology of this parasitoid are included.